2007
DOI: 10.1128/jb.01582-06
|View full text |Cite
|
Sign up to set email alerts
|

Quorum-Sensing Regulation of Adhesion in Serratia marcescens MG1 Is Surface Dependent

Abstract: Serratia marcescens is an opportunistic pathogen and a major cause of ocular infections. In previous studies of S. marcescens MG1, we showed that biofilm maturation and sloughing were regulated by N-acyl homoserine lactone (AHL)-based quorum sensing (QS). Because of the importance of adhesion in initiating biofilm formation and infection, the primary goal of this study was to determine whether QS is important in adhesion to both abiotic and biotic surfaces, as assessed by determining the degree of attachment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 60 publications
(54 reference statements)
3
89
0
2
Order By: Relevance
“…The same study found a role for certain genes, including bsmA, bsmB, and the type I fimbrial adhesin gene fimA, in the attachment of S. marcescens MG1 to immortalized corneal epithelial cells (31). Other studies have revealed the importance of quorum sensing regulation in biofilm maturation and biofilm-dependent protection against predation by protozoans (30,50,51).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…The same study found a role for certain genes, including bsmA, bsmB, and the type I fimbrial adhesin gene fimA, in the attachment of S. marcescens MG1 to immortalized corneal epithelial cells (31). Other studies have revealed the importance of quorum sensing regulation in biofilm maturation and biofilm-dependent protection against predation by protozoans (30,50,51).…”
mentioning
confidence: 82%
“…Surface proteins from cells grown overnight on LB plates at 30°C were prepared as previously described (31). Trichloroacetic acid-precipitated proteins were washed twice with cold acetone, dried, resuspended in 10 l of TE and 15 l of polyacrylamide gel electrophoresis (PAGE) sample buffer, boiled, and run on an 8 to 16% gradient gel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These adhesins probably interact with mannose glycoproteins expressed on the surface of corneal ep ithelial cells as a result of abrasion or trauma due to the use of contact lenses. [98]; identified type I fimbriae as the critical adhesin that mediate attachment of S. marcescens to human corneal epithelial cell surface. They also identified two AHL (N-acylhomoserine lactone)-regulated genes, bsmA and bsmB, to be involved in adhesion to biotic surface and the expression of these genes leads to the attachment of S. marcescens to HCE cells.…”
Section: Adhesionmentioning
confidence: 99%
“…Quorum sensing is also required for normal attachment and biofilm formation by the aquatic bacterium V. vulnificus (101). Interestingly, in some species, such as Serratia marcescens, the requirement for quorum-sensing regulation of attachment depends on the nature of the surface, with adherence to abiotic but not biotic surfaces being modulated by quorum sensing (87). Overall, the importance of quorum sensing in the regulation of cell-surface and cell-cell attachment has been repeatedly reported for a variety of other bacterial species, including E. coli, L. monocytogenes, Burkholderia cenocepacia, and Burkholderia cepacia (22,37,52,64,154).…”
Section: Figmentioning
confidence: 99%